2018
DOI: 10.1101/286807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription-dependent regulation of replication dynamics modulates genome stability

Abstract: Replication stress is a primary threat to genome stability and has been implicated in tumorigenesis1, 2. Common fragile sites (CFSs) are loci hypersensitive to replication stress3 and are hotspots for chromosomal rearrangements in cancers4. CFSs replicate late in S-phase3, are cell-type dependent4–6 and nest within very large genes4, 7–9. The mechanisms responsible for CFS instability are still discussed, notably the relative impact of transcription-replication conflicts7, 8, 10versus their low density in repl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…CFS were found to be enriched with large genes (McAvoy et al, 2007;Le Tallec et al, 2013) and for several CFSs, the expression level of the long gene was shown to associate with fragility (Blin et al, 2019;Helmrich et al, 2011;Wilson et al, 2015). Our analyses revealed that delayed RT in CFSs coincided with large genes, supporting the possibility that upon transcription, hazardous collisions between the replication and transcription machineries may occur disrupting fork progression leading to fragility.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…CFS were found to be enriched with large genes (McAvoy et al, 2007;Le Tallec et al, 2013) and for several CFSs, the expression level of the long gene was shown to associate with fragility (Blin et al, 2019;Helmrich et al, 2011;Wilson et al, 2015). Our analyses revealed that delayed RT in CFSs coincided with large genes, supporting the possibility that upon transcription, hazardous collisions between the replication and transcription machineries may occur disrupting fork progression leading to fragility.…”
Section: Discussionsupporting
confidence: 64%
“…Previously, expression of large genes has been suggested to associate and promote chromosomal instability at several CFSs (Helmrich et al, 2011;Wilson et al, 2015). However, a recent study reported that the expression level of very large genes affects their stability under replication, suggesting too little or too much transcription is not associated with fragility (Blin et al, 2019).…”
Section: Aph-induced Replication Delay Of Large Genes Is Associated Wmentioning
confidence: 99%
“…Transcription-mediated chase of initiation events has been reported in the bulk genes of various organisms [20][21][22][23][24] , which therefore shows that transcription shapes the replication initiation profile along transcribed sequences independently of their size and replication timing. However, fork slowing more drastically perturbs replication completion of loci replicated by long-traveling forks, a feature determined both by the size of the transcribed domain and by the degree of initiation paucity in the gene body, the latter property being controlled by the level of transcription 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this hypothesis, the role of transcription could be to chase origins from the gene body, as previously shown in various models [20][21][22][23][24] . A direct support to this view was recently provided by replacement of the endogenous promoter of three large genes with promoters of various strengths, which has shown that the transcription level dictates the density of initiation events across the gene body 25 . Many large transcribed genes however escape fragility indicating that, although important, transcription is not sufficient to set CFSs 8 .…”
Section: Introductionmentioning
confidence: 98%
“…The Debatisse lab found that high transcription of large genes resulted in a shift in their replication pattern from late to mid-S phase, likely giving the cells more time to complete synthesis of the regions before M phase. 193 The Smith lab reported that replication stress by HU results in redistribution of replication termination relative to transcription, setting up a situation where replication and transcription are no longer co-directional, so that head-on collisions are more likely to occur. 194 In cells exposed to oncogeneinduced replication stress, inappropriate activation of intergenic origins leads to transcription-replication conflicts and fork collapse.…”
Section: Some Very Recent Publications Have Connected Transcription Tomentioning
confidence: 99%